Optimization of Raising by the Intel Security Unit to Prevent the Vulnerability of Intolerant Group Conflict in the Jurisdiction Area of Boyolali Police (Advances in Police Science Research Journal, 2024)
Diversity is something that has long been inherent in the life of Indonesian society. One of the diversity that is prone to conflict is trust. Communities who adhere to different beliefs are certainly prone to conflict in this community, especially in the jurisdiction of the Boyolali Police. It can be seen from the many intolerant groups in the Boyolali Regency area where there is a lack of tolerance between differences in the Boyolali Regency area. From this attitude, intolerant groups carry out various disturbing activities such as holding demonstrations with no direction because they do not agree with government policies or the existence of these differences. The researcher discusses the efforts of the Intel Security Unit in mobilizing these groups in order to prevent the vulnerability of conflicts to occur in the jurisdiction of the Boyolali Police. This study uses POAC management theory (Planning, Organizing, Actuating, Controlling) and elements of 4M management (Man, Money, Material, Method). The results of the study found that there were factors that influenced the fundraising activities by the Intel Security Unit, namely that the personnel from the unit had not fully implemented vocational education or had no experience from the fundraising activities. Then it was also found that there were limitations to the facilities and infrastructure in fundraising such as vehicles or other assistive devices so that mobility in fundraising operations was hampered. The advice given to the Intel Security Unit is to provide opportunities for members to take part in vocational education or to hold forums aimed at sharing knowledge and experience from members who have served for a long time to members who have no experience. Then, with the limited facilities and infrastructure that are owned, one must take into account which one is more prioritized in fundraising operations so that mobili
Keywords: Optimalisasi, Unit Keamanan Intel, Penggalangan, Kelompok Intoleran